A Study Of Psychiatric Morbidty Amongst Children Attending A Child Guidance Clinic At A Tertiary Level Teaching Hospital In Nepal - Chapagai, Manisha; Dangol, Kabin Man; Tulachan, Pratiksha (Journal of Nobel Medical College, 2013)
Background: Mental health and its related problems are growing concerns over the world. The early onset of emotional and behavioral problem in the young children is related to a variety of health and behavior problems in adolescence. It is a challenging all over the world to determine the epidemiology of childhood mental disorders. Objective: The aim of this study is to sort out the prevalence and predominance of mental illness and their onset of age and sex among the child and adolescent who attended in the child guidance clinic in TUTH. Methodology: A retrospective study of a total of 539 consecutive cases of child and adolescent attended in Child Guidance Clinic TUTH. Diagnosis was made according to the criteria of Diagnostic and Statistical Manual of Mental Disorders, 4th edition, Text Revision. Result: The cases from the age of 0.4 year to 21 years with mean age 8.85±4.08 years. Significantly majority were boys (n=343, 63.6%) and most of from out of the Kathmandu valley (n=300, 53.2%). Significantly most case referred from ENT OPD of TUTH (n=97, 18%) and mental retardation was the commonest (n=81, 15%) followed by conversion disorder (n=77, 14.3%) and anxiety spectrum disorder (n=63, 11.7%) Conclusion: Boys are common in mental illness among child and adolescents. The common diagnoses among child and adolescent are mental retardation, conversion disorder, anxiety spectrum disorders and Autism spectrum disorder. Journal of Nobel Medical College Vol. 2, No.1 Issue 3 Nov.-April 2013 Page 55-63 DOI: http://dx.doi.org/10.3126/jonmc.v2i1.7677